Land-use rights of foreign-invested enterprises according to Vietnamese law - CHAU THI KHANH (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The provisions of Vietnamese law are presented, with a focus on the fundamental issues directly related to the land-use rights of foreign-invested enterprises, such as how land-use rights are established and the rights of foreign-invested enterprises in using land, the trading of rights for foreign-invested enterprises, and the securing of land-use rights of foreign-invested enterprises.Method: The term